On nonextendibility of series Dirichlet - Dagienė, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Е. Дагене. О непродолжаемости рядов Дирихле E. Dagienė. Apie Dirichle eilučių nepratęsiamumą